2018
DOI: 10.1111/ijau.12140
|View full text |Cite
|
Sign up to set email alerts
|

Shifting styles: Do auditor performance levels influence the review process?

Abstract: We examine communication behaviors during the audit review process using a survey of audit partners, managers, and in-charge/senior associates from each Big 4 accounting firm and one international accounting firm. We inquire about reviewers' preferred communication style when discussing review notes with preparers of varying performance levels, their likelihood of taking over the audit work of preparers due to either a lack of a response or an inappropriate response to a review note, and their propensity to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Senior auditors should be trained enough to detect any attempt to exercise premature sign-off by junior auditors (Hyatt and Taylor, 2013). Also, superior auditors have a critical role in assessing other auditors (Gimbar et al, 2018). It was concluded that the review process varies when the performance assessment is being prepared for above average or prepared for below average subordinates.…”
Section: Performance Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Senior auditors should be trained enough to detect any attempt to exercise premature sign-off by junior auditors (Hyatt and Taylor, 2013). Also, superior auditors have a critical role in assessing other auditors (Gimbar et al, 2018). It was concluded that the review process varies when the performance assessment is being prepared for above average or prepared for below average subordinates.…”
Section: Performance Appraisalmentioning
confidence: 99%
“…Downey (2018) states that offshoring of audit steps is a major factor in downgrading auditors performance. Gimbar et al (2018) argue that the review process using analytical procedures for identifying errors and generating hypotheses to resolve the misstatements is not being exercised properly. However, and to the best of our knowledge, the impact that performance appraisal poses on auditors' behaviour while considering cultural dimensions from a developed and a developing country as well as experienced and inexperienced auditors' behaviour has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we measure connectivity based on the ease of face‐to‐face communications between offices because previous research has shown that face‐to‐face meetings within audit teams are beneficial in the conduct of the audit (Tan and Libby [1997], Brazel, Agoglia, and Hatfield [2004], Vera‐Munoz, Ho, and Chow [2006], Gimbar et al. [2018]) and that directly observing an expert work is a more effective way to learn (Staszewski [2013]). Recent pandemic‐related events have limited in‐person interaction, with software such as Teams or Zoom used to simulate face‐to‐face communication.…”
Section: Discussionmentioning
confidence: 99%
“…Face‐to‐face communication is particularly important when transferring tacit knowledge (Tan and Libby [1997], Brazel, Agoglia, and Hatfield [2004], Ganesan, Malter, and Rindfleisch [2005], Vera‐Munoz, Ho, and Chow [2006], McCann [2007], Gimbar et al. [2018]) because “individuals are able to adapt and restructure knowledge so that it applies to new contexts” (Ganesan, Malter, and Rindfleisch [2005]). Ganesan, Malter, and Rindfleisch [2005] find that face‐to‐face communication is positively related to noncodified (tacit) knowledge acquisition.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%
“…We exclude journals on the ABDC list whose focus is primarily tax, managerial or financial accounting. Due to our focus on empirical research, we also exclude the Journal of Accounting Literature.9 Our identification of relevant research through search terms omits several types of studies; e.g., those that: (1) examine the effect on audit quality of factors not directly related to AFC, and do not propose AFC as a possible reason for findings (e.g., some studies of "contagion" of low audit quality across offices;Francis & Michas, 2013); (2) investigate individual differences as reason for variation in audit quality (e.g., auditor performance affecting the review process;Gimbar et al, 2018); and (3) compare audit procedures, without linking those procedures to culture (e.g., using computer mediation in fraud brainstorming;Lynch et al, 2009). We refer readers to more general reviews of the auditing literature (e.g.,Lennox, 2014;DeFond & Zhang, 2014;Andiola, 2014) that provide information about studies on each of our topics outside of the core concepts of AFC.6 C.T.Alberti et al…”
mentioning
confidence: 99%